Nigerian entrepreneurs in Istanbul, Turkey: spatial and temporal dimensions of mixed embeddedness - Baird, T (International Migration Institute, 2015)
This article analyses the macro-institutional framework, urban opportunity structure, and micro-level resources of Nigerian entrepreneurs in the Istanbul textile market. The paper argues that: (1) in a context of low initial capital, a limited legal framework, and ethno-racial distinction, Nigerian migrants are successfully building organisations as immigrant entrepreneurs in the textile trade of Istanbul, and (2) root causes for this growth stem from (a) Turkey’s fragmented categories of ethnonational citizenship which give space to unfamiliar ethnonational constructions and categories; (b) new economic divisions arising from the re-ordering of urban commercial space in Istanbul, and (c) temporal resources and strategies of individual migrants in shaping the urban opportunity structure. The article ends with a discussion of migrants as agents of change and directions for future research.